Pola Asuh Orang Tua Sebagai Prediktor dari Perilaku Anak Prasekolah - Hardika, Mufida Dian; Sundari, Sundari; Arwiyantasari, Wida Rahma (FORUM ILMIAH KESEHATAN, 2023)
Parenting is a method of consistent behavior that is applied to children from time to time. Thus, parenting patterns that are not in accordance with the child's needs and conditions often cause children to experience less than optimal development. During the preschool period commonly known as the